Designing and managing programs an effectiveness-based approach - Kettner, Peter M.; Moroney, Robert M. (Sage Publications, 2023)
"This classic text for social work and human services helps readers grasp the meaning and significance of measuring performance and evaluating outcomes. Hands-on and practical, Designing and Managing Programs incorporates the principles of effectiveness-based planning as it addresses the steps of designing, implementing, and evaluating a human services program at the local agency level. Written by leaders in the field, it guides students through the process from beginning to end. Meaningful examples--from problem analysis and needs assessment to evaluating effectiveness and calculating costs--enhance reader understanding of how concepts are implemented in the real world. The Sixth Edition contains new examples and references, and updates based on changes to federal regulations"